Opening Hours Decision and Competition in the Motor Vehicle Inspection Market - Osmis Habte (Lund University, School of Economics and Management, Department of Economics, 2017)
This paper examines the effect of competition on a firm's choice of opening hours in the motor vehicle inspection market. Competition affects the incentive inspection firms face when choosing opening hours, which influences the probability that consumers find service time that best matches their preferred time. We use 2SLS analyses to resolve the potential endogeneity of market entry decisions. Using a detailed monthly firm-level panel data for all inspection firms in Sweden, we find that increased competition, measured using both the number of firms in a geographic market and average distance to nearby competitors, leads to expanded opening hours. The probability that inspection firms offer services on weekends also increases with local competition.
Keywords: D22; L11; L84; 330; opening hours; competition; non-price competition; entry; motor vehicle inspection market